Attitudes, Belief, and Barriers of Indonesian Oncology Nurses on Providing Assistance to Overcome Sexuality Problem - Afiyanti, Yati (Nurse Media Journal of Nursing, 2017)
Background: Sexuality and problems related to sexuality have been identified as components of nursing care by the nursing profession, nurse educators, other disciplines and patients.Purpose: This study aimed to describe the attitudes and beliefs of the Indonesian oncology nurses towards providing sexual care for the patients with cancer.Methods: The study used a descriptive design. Using convenient sampling method, 135 oncology nurses from three hospitals in Jakarta, Indonesia participated in this study.Results: Over 85% of the nurses believed that discussing sexuality with patients is a taboo and private issue. More than 90% of nurses understood that giving a patient permission to talk about sexual concerns is a nursing responsibility. About 73.3% nurses had beliefs that most hospitalized patients are too sick to be interested in sexuality and agreed that sexuality should be discussed if only the patient initiates it. However, more than 70% of the nurses believed that the patients expect nurses to ask about their sexual concerns.Conclusion: This study revealed that inappropriate attitude and belief of nurses on sexuality aspect of their patients might become a barrier in facilitating the needs of cancer patients to manage the sexuality problem caused by cancer and the treatment. Nurses need to overcome those various barriers so that they can increase the quality of life of the cancer patients.